Peningkatan Kompetensi Tenaga Pendidik terhadap Prestasi Belajar Siswa di SMA Muhammadiyah 1 Taman - Erna Mufida; Hidayatullah Hidayatullah (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2020)
This research is based on the importance of the role of educators in optimizing student achievement in terms of knowledge or cognitive aspects, attitudes or affective aspects and skills or psychomotor aspects. Therefore, this study aims to describe the effect of increasing the competence of teachers on student achievement at SMA Muhammadiyah 1 Taman. The research method used is qualitative research with a phenomenological approach according to the data and facts found in the field directly not the result of presumptions or assumptions. The research was conducted at SMA Muhammadiyah 1 Taman where in the odd semester the student achievement was mostly still below the average parallel score for class XI and XII. Based on that, this school tried to improve the competence of its teaching staff including pedagogical competence, personality competence, social competence, and professional competence through training, habituation of positive things, deliberation and mentoring. Along with the increase in the competence of the teaching staff, it can be seen that student achievement in the even semester has also increased where students whose scores are above the average grade in class X increase by 7%, class XI increases by 12% and class XII increases by 11%. The conclusion of this study is that the improvement of the competence of the teaching staff includes pedagogical competence, personal competence, social competence and professional competence are closely related to the improvement of student achievement.